Modelling surface water dynamics in an Amazonian sub-basin: impacts of hydraulic geometry refinement. Issue 6 (26th April 2021) - Coelho, Clívia Dias; Silva, Demetrius David da; Moreira, Michel Castro; Filizola, Naziano Pantoja; Fleischmann, Ayan
ABSTRACT: This study describes the impacts of refinement of hydraulic geometry (HG) relationships in the hydrological MGB model applied to an Amazonian sub-basin (Purus River basin). To this end, HG relationships were developed for the entire basin and for hydrologically homogeneous regions, and their performances were compared with observed data and a global width and depth database. Two simulations were then performed using the MGB model: one using the refined HG relationships and the other using the global width and depth database. The simulated streamflow and water level estimates were compared with observed data. The results showed that HG relationships for the hydrologically homogeneous regions provided better estimates of hydraulic parameters for the basin, with Nash-Sutcliffe efficiency of 0.96 for width and 0.95 for depth, and its use provided an improvement in the performance of the hydrological modelling in some gauge stations, with an increase in the Nash-Sutcliffe efficiency between 18% and 65%.